Design, synthesis, and evaluation of substrate – analogue inhibitors of Trypanosoma cruzi ribose 5-phosphate isomerase type B. (15th January 2021) - Gonzalez, Soledad Natalia; Mills, Jonathan J.; Maugeri, Dante; Olaya, Christopher; Laguera, Breana L.; Enders, Jeffrey R.; Sherman, Julian; Rodriguez, Ana; Pierce, Joshua G.; Cazzulo, Juan José; D'Antonio, Edward L.
Graphical abstract: Abstract: Ribose 5-phosphate isomerase type B (RPI-B) is a key enzyme of the pentose phosphate pathway that catalyzes the isomerization of ribose 5-phosphate (R5P) and ribulose 5-phosphate (Ru5P). Trypanosoma cruzi RPI-B ( Tc RPI-B) appears to be a suitable drug-target mainly due to: (i) its essentiality (as previously shown in other trypanosomatids), (ii) it does not present a homologue in mammalian genomes sequenced thus far, and (iii) it participates in the production of NADPH and nucleotide/nucleic acid synthesis that are critical for parasite cell survival. In this survey, we report on the competitive inhibition of Tc RPI-B by a substrate – analogue inhibitor, Compound B (Ki = 5.5 ± 0.1 μM), by the Dixon method. This compound has an iodoacetamide moiety that is susceptible to nucleophilic attack, particularly by the cysteine thiol group. Compound B was conceived to specifically target Cys-69, an important active site residue. By incubating Tc RPI-B with Compound B, a trypsin digestion LC-MS/MS analysis revealed the identification of Compound B covalently bound to Cys-69. This inhibitor also exhibited notable in vitro trypanocidal activity against T. cruzi infective life-stages co-cultured in NIH-3T3 murine host cells (IC50 = 17.40 ± 1.055 μM). The study of Compound B served as a proof-of-concept so that next generation inhibitors can potentially be developed with a focus on using a prodrug group in replacement of the iodoacetamide moiety, thus representing an attractive starting point for the future treatment of Chagas' disease.